2005
DOI: 10.1088/0953-2048/18/11/010
|View full text |Cite
|
Sign up to set email alerts
|

Chemical solution growth of CeO2buffer and YBCO layers on IBAD-YSZ/Hastelloy templates

Abstract: Low-cost and commercially viable processes to fabricate coated conductors are necessary for application in electric-power technologies. We demonstrate the chemical solution growth of CeO2 buffer and YBCO layers on IBAD-YSZ/Hastelloy templates. Very good biaxially textured CeO2 buffer layers can be formed by the chemical solution method using inorganic cerium nitrate precursors. Through control of the solution molarity, very uniform, smooth, and dense CeO2 buffer layers can be obtained. Subsequently, the YBC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…However, the more intense (00l) reflections are still dominant. Wang et al [20] observed the same phenomenon when depositing CeO 2 on IBAD-YSZ/Hastelloy. The explanation may be associated with the recrystallization of the ABAD YSZ layer at the high temperature of 900 • C necessary for the suitable growth of MOD CZO.…”
Section: Characterization Of the Abad Ysz And Mod Czo Buffersmentioning
confidence: 60%
See 1 more Smart Citation
“…However, the more intense (00l) reflections are still dominant. Wang et al [20] observed the same phenomenon when depositing CeO 2 on IBAD-YSZ/Hastelloy. The explanation may be associated with the recrystallization of the ABAD YSZ layer at the high temperature of 900 • C necessary for the suitable growth of MOD CZO.…”
Section: Characterization Of the Abad Ysz And Mod Czo Buffersmentioning
confidence: 60%
“…For comparison, PLD-grown YBCO films of ∼1.0 µm on the same kind of ABAD YSZ/SS substrates reach J GB c ∼ 1.2-2.5 MA cm −2 (77 K) [26]. Regarding CSD-grown CCs, Wang et al [20] reported an all-chemical cap + YBCO architecture, TFA YBCO/ MOD CZO/ IBAD YSZ/hastelloy, with J GB c ∼ 1.2 MA cm −2 (77 K) for a 200 nm sample (I c = 24 A/cm-width). On the other hand, Izumi et al [27] reported I c values as high as 735 A/cm-width for 2 µm thick YBCO films, but the employed architecture, TFA YBCO/ PLD CZO/ IBAD GZO/hastelloy, required a PLDdeposited capping layer.…”
Section: Measurementsmentioning
confidence: 99%
“…The template and barrier layers are generally oxides, so a seed layer is needed to deposit on the surface of the metal substrate to help the crystallization and growth of oxides. In terms of the scheme selection of the buffer layer, the technical route of one, two, three, or even more layers is adopted [57][58][59][60][61] . The ultimate purpose is to play an influential role in preventing diffusion and providing a high-quality growth template.…”
Section: Structure and Preparation Methods Of 2g-hts Tapesmentioning
confidence: 99%